ANALISIS PENGGUNAAN E-COURT DI PENGADILAN NEGERI JAKARTA UTARA PERIODE 2022- 2023 BERDASARKAN PERATURAN MAHKAMAH AGUNG NOMOR 7 TAHUN 2022 DAN SIYASAH DUSTURIYAH - Paujiah, Syifa; Rahim, Abdur; Rohmah, Siti Ngainnur (Gapenas Publisher, 2025)
This thesis discusses the influence of the use of e-Court and its administrative effectiveness in the context of cultural transition from conventional to virtual trials. This change caused two reactions in the community that was previously used to conventional hearings , so it was necessary to adapt to the online system. These two reactions are used as the basis for the author's analysis of the e-Court mechanism from the perspective of siyasah dusturiyah. The purpose of this study is to find out the Analysis of the Use of E-Court and administrative arrangements in the North Jakarta District Court for the 2022-2023 Period Based on Supreme Court Regulation Number 7 of 2022. As well as analyzing the Use of E-Court in the North Jakarta District Court for the 2022-2023 Period Based on Siyasah Dusturiyah. This research uses a library research method with a normative-conceptual approach. Data collection was carried out through a systematic literature search of legal materials and academic studies. The data sources in the research were obtained from PERMA, Islamic legal literature, books, journals, and relevant articles. This study found that the use of e-Court in the North Jakarta District Court was in accordance with Perma No. 7 of 2022, starting from account registration, payment of case fees through virtual accounts, to setting trial schedules. For optimization, the North Jakarta District Court developed Sidilantara, Sigesittapus, and PASTI which accelerate administration, although system improvements, training, and digital security are still needed. From the perspective of siyasah dusturiyah, the implementation of e-Court (2022–2023) reflects the modernization of the judiciary that is in line with Islamic values and Pancasila, supporting justice, transparency, and public benefit in accordance with maqashid al-shariah, but still requires increasing digital literacy, data protection, and adaptation of legal culture